Surgical Treatment of a Case of Ledderhose’s Disease: A Safe Plantar Approach to Subtotal Fasciectomy - Bruno Gonçalves Schröder e Souza; Gilberto Zaquine de Souza Júnior; Raíssa Mansilla Cabrera Rodrigues; Diogo Stelito Rezende Dias; Valdeci Manoel de Oliveira (Case Reports in Orthopedics)
Plantar fibromatosis, Ledderhose’s disease, or Morbus Ledderhose is an uncommon benign nodular hyperplasia of the plantar aponeurosis. The aim of this paper was to report the case of a 47-year-old male patient who had concomitant Dupuytren’s disease and failed all conservative measures. He was treated surgically with prompt and complete relief of symptoms postoperatively, and he has had no recurrence at the 2-year follow-up. In this richly documented case, we discuss details of the surgical technique and anatomy, which was important for a successful outcome and preventing complications. The technique for subtotal fasciectomy is reviewed and the relevance of the adequate choice of skin incision to prevent painful scarring, skin necrosis, and difficulties with shoe wearing is highlighted.